PREVALENCE AND SEVERITY OF DENTAL FLUOROSIS AND ASSOCIATED ENVIRONMENTAL AND BEHAVIORAL FACTORS IN CHILDREN FROM A RURAL POPULATION - Rodriguez-Landauro, Ana Juliet (2026)
Introduction: Dental fluorosis is an enamel defect resulting from excessive fluoride exposure during amelogenesis. Its development arises from a multifactorial interaction between environmental, behavioral, and biological factors. In rural communities, lack of supervision during children’s toothbrushing and inappropriate use of fluoride toothpaste may increase the risk, even when water fluoride levels are low. Objective: To determine the association between environmental and behavioral factors with the presence and severity of dental fluorosis in children aged 6 to 12 years from the district of San Bartolome, province of Huarochiri, Department of Lima. Methods: A descriptive, cross-sectional study was conducted in a census sample of 110 schoolchildren. Dental fluorosis was clinically assessed using the Thylstrup and Fejerskov (TF) index. Water samples were analyzed to determine fluoride concentration (ppm), and structured questionnaires were administered to caregivers to evaluate oral hygiene practices. Statistical analysis included Fisher’s exact tests and bivariate logistic regression. Results: The prevalence of dental fluorosis was 93.6%, with TF2 (23.6%), TF3 (18.2%), and TF5 (17.3%) being the most frequent categories. The risk of fluorosis was significantly associated with age (p = 0.0004), age at brushing initiation (p = 0.0269), frequent toothpaste ingestion (p = 0.0010), use of adult toothpaste (p = 0.0018), and amount of toothpaste used (p < 0.0001). Regression models indicated greater severity among children aged 10 and 12 years, and a reduced risk among those who never ingested toothpaste (OR = 0.015; p = 0.0006) or used minimal amounts (OR = 0.001; p < 0.0001). Fluoride concentrations in drinking water ranged from 0.13 to 0.36 ppm, below the WHO recommended limit. Conclusion: Behavioral factors— such as early initiation of brushing, use of adult toothpaste, excessive application, and ingestion of dentifrice—account for the high prevalence and severity of dental fluorosis in this population, rather than environmental fluoride exposure. Strengthening parental education on the rational use of fluoridated toothpaste and supervised brushing during early childhood is recommended.